2022
DOI: 10.3389/fimmu.2022.1055466
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3+ regulatory T cell therapy for tolerance in autoimmunity and solid organ transplantation

Abstract: Regulatory T cells (Tregs) are critical for tolerance in humans. The exact mechanisms by which the loss of peripheral tolerance leads to the development of autoimmunity and the specific role Tregs play in allograft tolerance are not fully understood; however, this population of T cells presents a unique opportunity in the development of targeted therapeutics. In this review, we discuss the potential roles of Foxp3+ Tregs in the development of tolerance in transplantation and autoimmunity, and the available dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 193 publications
0
15
0
Order By: Relevance
“…Further, the induction of Tr1 cells could be a therapeutic lever that offers advantages over traditional FoxP3 + T reg therapies ( 40 ). While FoxP3 + T regs are essential for establishing tolerance ( 63 ), Tr1 cells have been identified as key players in sustaining this tolerance long-term ( 59 ). This understanding may reshape therapeutic strategies in SOT, with an emphasis on harnessing the unique properties of Tr1 cells to improve SOT outcomes.…”
Section: Cellular Therapeutic Strategies In Transplantation Patientsmentioning
confidence: 99%
“…Further, the induction of Tr1 cells could be a therapeutic lever that offers advantages over traditional FoxP3 + T reg therapies ( 40 ). While FoxP3 + T regs are essential for establishing tolerance ( 63 ), Tr1 cells have been identified as key players in sustaining this tolerance long-term ( 59 ). This understanding may reshape therapeutic strategies in SOT, with an emphasis on harnessing the unique properties of Tr1 cells to improve SOT outcomes.…”
Section: Cellular Therapeutic Strategies In Transplantation Patientsmentioning
confidence: 99%
“…A number of theories have been proposed in an attempt to explain the pathoetiology of classical autoimmune diseases, focusing on alterations in the B-cell antibody and cytokine production [22] and dysregulated suppressor cells, such as regulatory T cells (Treg) [23] and myeloid-derived suppressor cells (MDSC) [24]. Genetic risk factors predominantly include variants in MHC, immunoglobulins and T cell receptors, although not all susceptibility genes lead to an individual having an autoimmune disorder.…”
Section: Classical Autoimmunitymentioning
confidence: 99%
“…Therefore, induction of M2 macrophages by Treg-derived exosomes may promote tumor growth. Immunosuppression of Tregs mainly inhibits the activation and proliferation of CD4 + and CD8 + T cells ( 60 ). Studies have shown that exosomes derived from Tregs suppress T-cell proliferation ( 61 , 62 ).…”
Section: T Cell-derived Exosomes In Tumor Immune Modulationmentioning
confidence: 99%